Penggunaan Sarana Non Penal melalui Tim Pengawalan, Pengamanan Pemerintahan dan Pembangunan Daerah (TP4D) dalam Pengelolaan Dana Desa sebagai Upaya Pencegahan Tindak Pidana Korupsi di Kabupaten Rokan Hilir - Megonondo, Sri Odit (Magister (S2) Ilmu Hukum Fakultas Hukum Universitas Riau, 2019)
Corruption must be regarded as an extraordinary crime (extraordinary crime) which therefore requires extraordinary effort to eradicate it. The effort to eradicate corruption consists of two major parts, namely action, and prevention. One of the efforts to eradicate corruption, especially from the preventive aspects carried out by the Attorney General's Office is the establishment of Government Guards and Regional Safeguards and Regional Development (TP4D).To find out the use of non-reasoning facilities through TP4D in managing village funds in Rokan Hilir Regency and to find out the causes of irregularities or misuse in the management of village funds in Rokan Hilir Regency, a type of sociological legal research is established, namely research carried out directly in the field or research sites.The use of non-reasoning facilities through TP4D in managing village funds as an effort to prevent corruption in Rokan Hilir Regency is carried out in the form of consultation, socialization, coordination with other government elements, and mentoring by going directly to the field. The cause of the occurrence of irregularities or misuse in the management of village funds in Rokan Hilir Regency is due to the number and distance of the trip. Kepenghuluan in Rokan Hilir Regency amounted to 178 with the distance between one kepenghuluan with other kepenghuluan very far so that the time or distance to carry out assistance in the scope of prevention of corruption acts non-penal is not often done. Another cause is the perspective of the headmaster who considers ADD and DD as part of the budget allocated to the headmaster, the weak repressive law enforcement, especially in the case of the limited authority possessed by the Rokan Hilir District TP4D, namely the necessity of coordinating with the Government Internal Supervisory Apparatus (APIP), and the lack of knowledge of the head of the government administration. The solution to minimize the deviation or abuse is to realize the values of anti-corruption to all principals as an effort to prevent corruption.